Knowledge, Attitude, and Risk Perception Associated with Malaria Control Among Workers in Indonesia's New Capital City - Raden Mohammad Pradendi Nikita Sangaji; Yunianto Setiawan; Ike Anggraeni Gunawan (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Malaria remains a public health concern in Indonesia, particularly in Indonesia's New Capital City (IKN) development area, where environmental changes and worker mobility may increase transmission risk. This study aimed to examine the association between knowledge, attitude, risk perception, and malaria control among workers in the IKN area. A cross-sectional study was conducted among 167 workers in the IKN development area, East Kalimantan, Indonesia. Data were collected using validated self-administered questionnaires. Chi-square tests were used to examine bivariate associations, and multiple binary logistic regression was performed to identify the strongest factor associated with malaria control behavior. Most respondents had moderate knowledge (46.7%), positive attitudes (57.5%), good risk perception (55.1%), and good malaria control behavior (54.5%). Knowledge (p=0.001), attitude (p=0.001), and risk perception (p=0.001) were significantly associated with malaria control. Multivariate analysis showed that risk perception was the strongest determinant (OR=8.559; 95% CI=3.184-23.004), followed by knowledge (OR=6.309; 95% CI=2.145-18.552) and attitude (OR=4.558; 95% CI=1.732-11.994). Knowledge, attitude, and risk perception were significantly associated with malaria control among IKN workers, with risk perception emerging as the dominant factor. These findings contribute evidence for strengthening workplace-based malaria prevention through contextual health education, routine risk communication, early screening, and environmental control in rapidly developing occupational settings.